Use of Five Nitrogen Source and Placement Systems for Improved Nitrogen Management of Irrigated Corn. Issue 6 (3rd November 2016) - Shapiro, Charles; Attia, Ahmed; Ulloa, Santiago; Mainz, Michael
Abstract : Core Ideas: Slow‐release fertilizers improve the synchronization of N release and crop needs. Applying N source in a band conserves N for greater corn yield and N uptake. Chlorophyll readings and stalk NO3 –N are useful tools for improving corn N management. Improved N management for corn ( Zea mays L.) production is necessary to maintain N in the root zone for greater yield and N uptake. Three field experiments were conducted in Nebraska on Thurman loamy sand at Concord in 2008, on Alcester silty clay loam at Haskell Agricultural Laboratory (HAL) in Concord in 2009, and on Hord silt loam at Pierce in 2009. Treatments included four N rates (56, 112, 168, and 224 kg N ha −1 ) and five N‐source–placement systems. The five N systems were broadcast polymer‐coated urea (PCU), broadcast urea–NH4 NO3 (UAN), a broadcast 7:3 mixture of UAN and Nitamin–Nfusion (NF), band UAN, and band NF. Each trial included a zero‐N control. Only Concord had significant precipitation within 21 d after fertilizer application (141 mm). Results indicated that use of broadcast PCU and band NF had slight but N‐conserving effects as measured by plant indicators. Band NF had 3% greater SPAD reading and 47% greater stalk NO3 –N compared with broadcast UAN across sites. Corn fertilized with broadcast PCU produced 4 to 13% (0.5–1.8 Mg ha −1 ) greater grain yield and 7% greater grain and plant‐N uptake at Concord and HAL compared with broadcast UAN. Band NF increased grain yield by 4% (0.6 Mg ha −1 ) at Concord and Pierce and plant‐N uptake by 7% at Concord compared with broadcast UAN. The use of slow‐release fertilizers is a risk reduction strategy when weather is conductive to N losses; otherwise, they performed similarly to UAN.